Ahli Majlis Bandaraya Kuching Selatan (MBKS) : satu analisis terhadap profil individu yang menjadi ahli majlis (MBKS) - Goh, Chow Ling (University Malaysia Sarawak (UNIMAS), 2003)
Elite groups are always influence in all sorts of societies. The study aims to investigate whether the member of Majlis Bandaraya Kuching Selatan (Kuching City South Municipal) are member of elite group. For this purpose, the research is looking at the family background of the members of Majlis Bandaraya Kuching Selatan (MBKS), their education level, the involvement in politics, economic and social activities.